Globalisation of tobacco industry influence and new global responses - Yach, D. (BMJ Group, 2000)
The globalisation of tobacco marketing, trade, research, and industry influence represents a major threat to public health worldwide. Drawing upon tobacco industry strategy documents prepared over several decades, this paper will demonstrate how the tobacco industry operates as a global force, regarding the world as its operating market by planning, developing, and marketing its products on a global scale. The industry has used a wide range of methods to buy influence and power, and penetrate markets across the world. It has an annual turnover of almost US$400 billion. In contrast, until recently tobacco control lacked global leadership and strategic direction and had been severely underfunded. As part of moving towards a more sustainable form of globalisation, a global enabling environment linked to local actions should focus on the following strategies: global information management; development of nationally and locally grounded action; global regulation, legal instruments, and foreign policy; and establishment of strong partnerships with purpose. As the vector of the tobacco epidemic, the tobacco industry's actions fall far outside of the boundaries of global corporate responsibility. Therefore, global and local actions should not provide the tobacco industry with the two things that it needs to ensure its long term profitability: respectability and predictability.   Keywords: globalisation of tobacco marketing